2016
DOI: 10.1371/journal.pone.0161076
|View full text |Cite
|
Sign up to set email alerts
|

Parasite Removal, but Not Herbivory, Deters Future Parasite Attachment on Tomato

Abstract: Plants face many antagonistic interactions that occur sequentially. Often, plants employ defense strategies in response to the initial damage that are highly specific and can affect interactions with subsequent antagonists. In addition to herbivores and pathogens, plants face attacks by parasitic plants, but we know little about how prior herbivory compared to prior parasite attachment affects subsequent host interactions. If host plants can respond adaptively to these different damage types, we predict that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Variation in size within host species is another factor that may influence host selection, as it was found that Cuscuta preferentially parasitises tall plants over short ones (Marquardt & Pennings, 2010). It was also observed that prior dodder parasitism and herbivory events can, depending on the host species, reduce subsequent attachment, suggesting that Cuscuta preferences may be influenced by the identity and the outcome of the initial attack, and that induced physiological changes in potential hosts may have a repellent effect on Cuscuta (Tjiurutue et al, 2016(Tjiurutue et al, , 2017. It should be pointed out that parasitism varies in intensity for a given host species between different environments, shaping its preferred status in a given location (Baráth, 2021).…”
Section: Cuscuta Selectively Forages For Potential Hostsmentioning
confidence: 99%
“…Variation in size within host species is another factor that may influence host selection, as it was found that Cuscuta preferentially parasitises tall plants over short ones (Marquardt & Pennings, 2010). It was also observed that prior dodder parasitism and herbivory events can, depending on the host species, reduce subsequent attachment, suggesting that Cuscuta preferences may be influenced by the identity and the outcome of the initial attack, and that induced physiological changes in potential hosts may have a repellent effect on Cuscuta (Tjiurutue et al, 2016(Tjiurutue et al, , 2017. It should be pointed out that parasitism varies in intensity for a given host species between different environments, shaping its preferred status in a given location (Baráth, 2021).…”
Section: Cuscuta Selectively Forages For Potential Hostsmentioning
confidence: 99%